The effectiveness of smoking prevention module towards knowledge and smoking refusal skill among secondary school students in Kota Bharu, Kelantan - Anuar, Norlina (2018)
Background : Currently, smoking initiation in the adolescents is becoming more common. To our knowledge, besides ‘Kelab Doktor Muda’ programme, there is no other smoking prevention modules specifically targeting adolescents in Malaysia. Such modules are important to reduce the number of smoking in adolescents. Assessing the efficacy of these smoking prevention programmes is equally important to ensure the benefits are received by the adolescents. Objectives : To study the effectiveness of the smoking prevention module towards knowledge on smoking and its harmful effects and smoking refusal skill among secondary school students in Kota Bharu, Kelantan. Methods : A quasi experimental interventional study was conducted from August until October 2016, involving 166 participants, aged 13 to 14 years old who were non smokers. 83 students from SMK Kubang Kerian 3 were allocated to the intervention group which received the smoking prevention module. Another 83 students from SMK Ketereh were allocated to the control group which only received the smoking prevention module after the study had been completed. The knowledge on smoking and its harmfuleffects and smoking refusal skill score were assessed using a set of questionnaires at baseline, 2 weeks and 8 weeks after the intervention. Repeated measure ANCOVA was used to analyse the mean score difference of both groups at baseline and after intervention. Results : There were significant improvement in the knowledge on smoking and its harmful effects and smoking refusal skill mean score among the intervention group as compared to the control group. For the analysis of the mean score of knowledge, there was no significant difference of the baseline score between the intervention and control group (p = 0.713. On the other hand, after intervention, there was significant increment of the knowledge score in the intervention group with significant difference in crude mean and estimated marginal means of knowledge score between intervention and control group after controlling for sex [F(df) = 15.96(1.5), p <0.001]. For the analysis of smoking refusal skill score, there was significant statistical difference in mean baseline refusal skill score between the two groups (p = 0.003). After the intervention, there was significant increment of the refusal skill score in the intervention group with significant difference in crude mean and estimated marginal means of smoking refusal skill score between intervention and control group after controlling for sex [F(df) 5.66(1.8), p = 0.005]. Conclusion : This smoking prevention module increased the level of knowledge on smoking and its harmful effects and smoking refusal skill among the secondary school students. Thus, it is advocated to be used as one of the standard modules to improve the current method of teaching in delivering knowledge related to harmful effects ofsmoking, laws related to smoking and smoking refusal skill to the secondary school students in Malaysia.